Synthetic AAV/CRISPR vectors for blocking HIV‐1 expression in persistently infected astrocytes. Issue 2 (9th November 2017) - Kunze, Christine; Börner, Kathleen; Kienle, Eike; Orschmann, Tanja; Rusha, Ejona; Schneider, Martha; Radivojkov‐Blagojevic, Milena; Drukker, Micha; Desbordes, Sabrina; Grimm, Dirk; Brack‐Werner, Ruth
Abstract: Astrocytes, the most abundant cells in the mammalian brain, perform key functions and are involved in several neurodegenerative diseases. The human immunodeficiency virus (HIV) can persist in astrocytes, contributing to the HIV burden and neurological dysfunctions in infected individuals. While a comprehensive approach to HIV cure must include the targeting of HIV‐1 in astrocytes, dedicated tools for this purpose are still lacking. Here we report a novel Adeno‐associated virus‐based vector (AAV9P1) with a synthetic surface peptide for transduction of astrocytes. Analysis of AAV9P1 transduction efficiencies with single brain cell populations, including primary human brain cells, as well as human brain organoids demonstrated that AAV9P1 targeted terminally differentiated human astrocytes much more efficiently than neurons. We then investigated whether AAV9P1 can be used to deliver HIV‐inhibitory genes to astrocytes. To this end we generated AAV9P1 vectors containing genes for HIV‐1 proviral editing by CRISPR/Cas9. Latently HIV‐1 infected astrocytes transduced with these vectors showed significantly diminished reactivation of proviruses, compared with untransduced cultures. Sequence analysis identified mutations/deletions in key HIV‐1 transcriptional control regions. We conclude that AAV9P1 is a promising tool for gene delivery to astrocytes and may facilitate inactivation/destruction of persisting HIV‐1 proviruses in astrocyte reservoirs. Main Points: There is a growing interest in astrocytes as reservoirs for HIV‐1 in the brain. We identify a new vector (AAV9P1) for targeting human astrocytes and show the use of AAV9P1 for inactivation of latent HIV‐1 proviruses by CRISPR/Cas9 gene editing.